Epidemiology of Hepatitis B in Canada - Jun Zhang; Shimian Zou; Antonio Giulivi (Canadian Journal of Infectious Diseases)
OBJECTIVE: To provide a current and comprehensive review of the epidemiology of hepatitis B virus (HBV) in Canada.